Dopant‐Free Hole‐Transport Material with a Tetraphenylethene Core for Efficient Perovskite Solar Cells. Issue 8 (3rd March 2017) - Zhu, Hongwei; Zhang, Fei; Liu, Xicheng; Sun, Mengna; Han, Jianlei; You, Jing; Wang, Shirong; Xiao, Yin; Li, Xianggao
Abstract: A hole‐transport material (HTM), 1, 1, 2, 2‐tetrakis[4‐(3, 6‐di‐ tert ‐butyl‐9 H ‐carbazol‐9‐yl)phenyl]ethene (TTBCPE), was prepared straightforwardly and employed in the fabrication of perovskite solar cells (PSCs). The investigated HTM with tetraphenylethene as the core and tert ‐butylcarbazole as terminal units was synthesized in two steps from commercially available and cheap raw materials. The devices based on TTBCPE without the use of any dopants and additives exhibited a power conversion efficiency (PCE) of 12.65 %, which is comparable to 14.46 % obtained by using devices based on 2, 2′, 7, 7′‐tetrakis( N, N ′ ‐ di‐ p ‐methoxyphenylamino)‐9, 9′‐spirobifluorene ( p ‐doped spiro‐OMeTAD). Importantly, the device based on TTBCPE showed a higher stability than devices based on doped spiro‐OMeTAD if stored under ambient conditions. In this regard, this easily synthesized and dopant‐free system paves a new way to develop low‐cost HTMs. Abstract : The hole truth : A dopant‐free hole‐transport material, 1, 1, 2, 2‐tetrakis[4‐(3, 6‐di‐ tert ‐butyl‐9 H ‐carbazol‐9‐yl)phenyl]ethene (TTBCPE), is developed for perovskite solar cells, which exhibit a power conversion efficiency (PCE) up to 12.56 %. Importantly, the device based TTBCPE shows a higher stability than the devices based on doped 2, 2′, 7, 7′‐tetrakis( N, N ′ ‐ di‐ p ‐methoxyphenylamino)‐9, 9′‐spirobifluorene if stored under ambient conditions.